Competency-based training for Vietnamese civil servants - Ngo Sy Trung (Journal of State Management, 2024)
To better serve the people, Vietnam urgently needs administrative reform and implementation of national digital transformation goals to build a digital civil service, an e-government, and a digital government. Through this process, training for civil servants is also essential so that they have not only appropriate knowledge and skills for administrative reform but also digital technology to meet the new requirements of the civil service. This study focuses on the theory of competency-based training for civil servants to meet the requirements of administrative reform and digital transformation in Vietnam. The research objectives have been achieved mainly by qualitative methods, such as collecting and analysing secondary documents, so that issues on state policies can be discussed, and then innovations to promote the effectiveness of civil servant training in Vietnam can be suggested.